2016
DOI: 10.1089/bfm.2016.0017
|View full text |Cite
|
Sign up to set email alerts
|

Association of Etonogestrel-Releasing Contraceptive Implant with Reduced Weight Gain in an Exclusively Breastfed Infant: Report and Literature Review

Abstract: Background: Studies have not found that hormonal contraceptive implants adversely affect breastfeeding, but theoretical concerns exist. Methods: We reported a case of reduced weight gain in an exclusively breastfed infant in association with placement of (ENG)-releasing contraceptive implant (Nexplanon) to the FDA Adverse Events Reporting System (FAERS). We further queried reports to FAERS and reviewed published studies of the ENG implant during breastfeeding. Results: A breastfeeding mother received an ENG im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…20 The literature also includes one case report of abrupt infant growth deceleration and decreased maternal milk supply after initiation of an ENG implant at postpartum day 39 in the United States. 22 The authors of this case found an additional report of decreased breast milk production after placement of an ENG implant in the U.S. Food and Drug Administration's Adverse Event Reporting System. If a causal association between progestin implants and lactation failure does exist, the incidence is likely very low and could possibly be an issue for women who have other predisposing factors for lactation failure.…”
Section: Discussionmentioning
confidence: 91%
“…20 The literature also includes one case report of abrupt infant growth deceleration and decreased maternal milk supply after initiation of an ENG implant at postpartum day 39 in the United States. 22 The authors of this case found an additional report of decreased breast milk production after placement of an ENG implant in the U.S. Food and Drug Administration's Adverse Event Reporting System. If a causal association between progestin implants and lactation failure does exist, the incidence is likely very low and could possibly be an issue for women who have other predisposing factors for lactation failure.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, breastfeeding seems to not be affected by the hormonal system, and no negative effects have been reported [1]. A case report published in 2016 [184] showed a reduced weight gain in a breastfed infant of a mother receiving the implant 4 weeks after partum; more recently, Carmo et al [185] in an open RCT observed no significant difference at 12 months among breastfed infants whose mothers underwent early or delayed post-partum insertion of the ENG implant [185]. In two Cochrane systematic reviews [166,182], the ENG-releasing implant effects on lactation and infant growth were investigated; no significant differences in breastfeeding duration, breast milk composition, or infant growth were observed after comparison with other hormonal contraceptives [182]; similarly, no difference in breastfeeding rate at six months between immediate and delayed post-partum implant insertion was observed [166].…”
Section: Post-partum Implant Placementmentioning
confidence: 94%
“…The etonogestrel implant does not compromise breast milk quality; however, small amounts of etonogestrel are secreted in breast milk. Based on published data, the risk of lactation inhibition with the etonogestrel implant is approximately 0.9% [ 40 ]. Assuming a daily milk intake of 150 mL/kg, infants consume an average daily dose of about 19.9 ng/kg/day of etonogestrel after 1 month, decreasing to 15.1 ng/kg/day after 2 months and 10.5 ng/kg/day after 4 months of implant use.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a milk intake of 150 mL/kg bw, infants may ingest an average of 27 ng/kg bw/day after one month, which corresponds to approximately 2.2% of the maternal daily dose, calculated relative to body weight, and about 0.2% of the estimated absolute maternal daily dose. The concentration of etonogestrel in breast milk during breastfeeding decreases over time [ 40 , 41 ].…”
Section: Tablementioning
confidence: 99%